A Case of Perforated Cholecystitis into a Parastomal Hernia. (3rd October 2022) - Seang, Sereibanndith; Hort, Amy; Gosal, Preet K. S.; Richardson, Mark
Abstract : Introduction . Parastomal hernia is a common complication following an enterostomy. Gallbladder herniation into parastomal hernia is rare and may become symptomatic and inflamed and very rarely can lead to gallbladder perforation. We present the first case of gallbladder perforation inside a parastomal hernia with a unique skin change. Case Description . In this report, an 87-year-old female with a history of previous open cystectomy and ileal conduit formation, presented with right upper quadrant pain and worsening parastomal swelling. A computed tomography scan showed a parastomal herniation of the gallbladder, cholelithiasis, and possible early acute cholecystitis. Within 12 hours of admission, bile staining skin changes developed around her urostomy site which raised our suspicion of a perforated gallbladder. Biliary peritonitis was confirmed on laparoscopy the same day. We proceeded with an open midline cholecystectomy without hernia repair. The patient was well at her last follow-up. Discussion . A literature review found 14 published cases of incarcerated gallbladder hernia. This uncommon condition mainly affects elderly females. Ten cases were managed operatively, and four cases were managed nonoperatively, with good outcomes. Currently, no consensus on treatment guidelines exists. In a frail elderly patient, a nonoperative approach may be suitable. Operative management was indicated in this case due to clinical concerns of perforation due to developing skin changes. This cutaneous sign has not been previously documented in the literature. Conclusion . While rare, the gallbladder can herniate and become incarcerated inside a parastomal hernia. Bile staining of the skin should raise clinical suspicion of perforation. Management options depend on patient and pathology factors and can be nonoperative or operative, with or without hernia repair.